A Cross-Sectional Study of the Relationship Between Exercise, Physical Activity, and Health-Related Quality of Life Among Japanese Workers - Sugano, Ryosuke; Ikegami, Kazunori; Eguchi, Hisashi; Tsuji, Mayumi; Tateishi, Seiichiro; Nagata, Tomohisa; Matsuda, Shinya; Fujino, Yoshihisa; Ogami, Akira (Frontiers in Sports and Active Living, 2022)
Background: Studies have determined that exercise and physical activity positively affect physical and mental health, and that healthy workers contribute to increased work performance. The relationship between the time spent on exercise during leisure time and physical activity, including work, with health-related quality of life (HRQOL) in workers is unclear, with variations observed between occupational types. This cross-sectional study examined these associations among Japanese workers from various occupations during the COVID-19 pandemic. Methods: An Internet-based national health survey—Collaborative Online Research on Novel-coronavirus and Work-study (CORoNaWork study)—was conducted among 33,087 Japanese workers in December 2020. After excluding invalid responses, 27,036 participants were categorized into four and five groups according to exercise and physical activity time, respectively. Each group’s scores were compared on each of the four questions on the Japanese version of the Centers for Disease Control and Prevention Health-Related Quality of Life (CDC HRQOL-4) using generalized linear models. Age-sex adjusted and multivariate models were used to compare each index of the CDC HRQOL-4. Results: Compared to the reference category (almost never), any level of exercise (ORs 0.56 to 0.77) and physical activity (ORs 0.93 to 0.88) were associated with better self-rated health in the multivariate model. Any exercise was also associated with significantly reduced odds for physically or mentally unhealthy days; however, high levels of physical activity (≥120 minutes/day) were associated with significantly increased odds for these outcomes (ORs = 1.11 and 1.16, respectively). Conclusions: The results suggest that exercise habits are more critical to workers’ HRQOL than physical activity. Interventions that encourage daily exercise even for a short time are likely to be associated with better workers' health and work performance.